2012
DOI: 10.1080/02640414.2012.667879
|View full text |Cite
|
Sign up to set email alerts
|

Striving for success or addiction? Exercise dependence among elite Australian athletes

Abstract: Exercise dependence is a condition that involves a preoccupation and involvement with training and exercise, and has serious health and performance consequences for athletes. We examined the validity of a biopsychosocial model to explain the development and maintenance of exercise dependence among elite Australian athletes. Participants were 234 elite Australian athletes recruited from institutes and academies of sport. Thirty-four percent of elite athletes were classified as having exercise dependence based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 21 publications
5
63
2
5
Order By: Relevance
“…The prevalence of REA was 4.2% in the present study which is similar to the values reported for leisure exercisers elsewhere in the literature ranging from 1.9 to 3.2% (Szabo et al 2015). However, it is lower than that reported for athletic populations ranging between 17.0 and 41.4% (Blaydon and Lindner 2002;Costa et al 2015;McNamara and McCabe 2012). Indeed, such Bexaggerated^prevalence rates prompted Szabo et al (2015) to question the interpretation of the EAI items by elite athletes who score unusually high on this tool and may simply reflect their passion for exercise rather than addiction.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The prevalence of REA was 4.2% in the present study which is similar to the values reported for leisure exercisers elsewhere in the literature ranging from 1.9 to 3.2% (Szabo et al 2015). However, it is lower than that reported for athletic populations ranging between 17.0 and 41.4% (Blaydon and Lindner 2002;Costa et al 2015;McNamara and McCabe 2012). Indeed, such Bexaggerated^prevalence rates prompted Szabo et al (2015) to question the interpretation of the EAI items by elite athletes who score unusually high on this tool and may simply reflect their passion for exercise rather than addiction.…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, the current findings-supporting and expanding the few recent research results-call for the differentiation of REA from passion while the moderators of the relationship between the two are also identified. Such work in the field is necessary, because the difference in the reported exaggerated prevalence rates in competitive/elite athletes, ranging between 17.0 and 41.4% (Blaydon and Lindner 2002;Costa et al 2015;McNamara and McCabe 2012) in contrast to the rates of REA in the general population (0.5%) as based on the only population-wide representative study (Monók et al 2012), shows that there is a conceptual confound in the field of exercise addiction. Knowing about the involvement of passion in REA, mediating role of exercise volumes and intensity will help facilitate future systematic research aimed at conceptual clarification of REA.…”
Section: Discussionmentioning
confidence: 99%
“…The primary aim was to address the acknowledged lack of consistency in maladaptive exercise measurement (Davis et al, 1997; Hausenblas & Symons Downs, 2002b; Mónok et al, 2012). The FIT Index was an early example of such a measure, while the Exercise Dependence Scale (EDS) and the Obligatory Exercise Questionnaire (OEQ) were also used.…”
Section: Discussionmentioning
confidence: 99%
“…Participation in physical activity has long been encouraged for its mental and physical benefits (Kirkcaldy & Shephard, 1990; Loumidis & Wells, 1998; Mónok et al, 2012). Due to such benefits, excessive exercise was first thought to be a ‘positive addiction’, with no harmful consequences (Glasser, 1976).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation